2017
DOI: 10.3183/npprj-2017-32-04-p550-571
|View full text |Cite
|
Sign up to set email alerts
|

Structural changes of lignin in biorefinery pretreatments and consequences to enzyme-lignin interactions - OPEN ACCESS

Abstract: The main target of a biorefinery pretreatment process is to break down the ligninreinforced plant cell wall structure prior to enzymatic hydrolysis of polysaccharides to fermentable sugars. Various physico-chemical alterations occur in lignin during the biomass pretreatment, but effects of those structural changes on subsequent enzymatic hydrolysis have remained ambiguous. We review the reinforcing and detrimental lignin-enzyme interactions and their underlying mechanisms, and use this structure-function infor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
20
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 39 publications
(20 citation statements)
references
References 182 publications
0
20
0
Order By: Relevance
“…The efficient valorization of lignin has been hampered by its complex and varying chemical structure partly arising from chemical reactions during these pulping [1][2][3] and biomass pretreatment processes. 4 In effect, cleavage of the inter-unit linkages of native lignin (Fig. 1c-h) and associated formation of new covalent bonds leads to technical lignins with complex and incompletely elucidated structures.…”
Section: Monika öSterbergmentioning
confidence: 99%
See 1 more Smart Citation
“…The efficient valorization of lignin has been hampered by its complex and varying chemical structure partly arising from chemical reactions during these pulping [1][2][3] and biomass pretreatment processes. 4 In effect, cleavage of the inter-unit linkages of native lignin (Fig. 1c-h) and associated formation of new covalent bonds leads to technical lignins with complex and incompletely elucidated structures.…”
Section: Monika öSterbergmentioning
confidence: 99%
“…Nevertheless, one needs to be critical as to when the energy input and solvents used for the production of LNPs is compensated by the added value of the products. Other issues that are not always addressed are (1) to what extent the processes are preventing the formation of waste, especially wastewater, (2) what is the atom efficiency of the process, (3) are all materials incorporated in the product, and (4) to what extent could LNPs be designed for degradation?…”
Section: Monika öSterbergmentioning
confidence: 99%
“…The structure of a specific lignin material strongly depends on the botanical origin and the isolation process. Especially the harsh thermochemical processes used to separate cellulose from other cell‐wall components cause fragmentation, functional group eliminations, and process‐typical chemical functionalization of lignin . In recent years, apart from its combustion for energy, isolation of lignin originating from industrial kraft pulping processes as well as biorefinery plants producing ethanol as biofuel has seen a steady increase.…”
Section: Introductionmentioning
confidence: 99%
“…Lignin has been considered as one of the major obstructions in biorefinery operations aiming at enzymatically converting cellulose in lignocellulosic biomass into glucose before further downstream processing (Li, Pu, & Ragauskas, ). Nonproductive adsorption of cellulases onto lignin is considered an important mechanism behind retardation of enzymatic cellulose degradation in lignocellulose‐based processes (Liu, Sun, Leu, & Chen, ; Saini, Patel, Adsul, & Singhania, ; Sipponen et al, ). Studies have reported adsorption of cellulases onto lignin isolated from various biomass feedstocks and have correlated such adsorption with the observed retardation of enzymatic degradation of pure model cellulose in the presence of the isolated lignin (Kellock, Rahikainen, Marjamaa, & Kruus, ; Rahikainen et al, ; Tu, Pan, & Saddler, ).…”
Section: Introductionmentioning
confidence: 99%
“…Hydrophobic interaction (Sammond et al, ; Tu et al, ), electrostatic interaction (Lan, Lou, & Zhu, ; Yarbrough et al, ), and hydrogen bonding (Sewalt, Glasser, & Beauchemin, ; Yu et al, ) have been regarded as the cause of the nonproductive binding of cellulases to lignin. However, more recently, it has been recognized that several interactions between the different chemical groups in the lignin and in the enzymes may be occurring simultaneously (Liu et al, ; Nakagame, Chandra, Kadla, & Saddler, ; Rahikainen, Evans et al, ; Sipponen et al, ).…”
Section: Introductionmentioning
confidence: 99%